SRSF1-dependent nuclear export inhibition of C9ORF72 repeat transcripts prevents neurodegeneration and associated motor deficits. - Hautbergue, G.M.; Castelli, L.M.; Ferraiuolo, L.; Sanchez-Martinez, A.; Cooper-Knock, J.; Higginbottom, A.; Lin, Y.H.; Bauer, C.S.; Dodd, J.E.; Myszczynska, M.A.; Alam, S.M.; Garneret, P.; et al. (Nature communications, 2017)
Hexanucleotide repeat expansions in the C9ORF72 gene are the commonest known genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia. Expression of repeat transcripts and dipeptide repeat proteins trigger multiple mechanisms of neurotoxicity. How repeat transcripts get exported from the nucleus is unknown. Here, we show that depletion of the nuclear export adaptor SRSF1 prevents neurodegeneration and locomotor deficits in a Drosophila model of C9ORF72-related disease. This intervention suppresses cell death of patient-derived motor neuron and astrocytic-mediated neurotoxicity in co-culture assays. We further demonstrate that either depleting SRSF1 or preventing its interaction with NXF1 specifically inhibits the nuclear export of pathological C9ORF72 transcripts, the production of dipeptide-repeat proteins and alleviates neurotoxicity in Drosophila, patient-derived neurons and neuronal cell models. Taken together, we show that repeat RNA-sequestration of SRSF1 triggers the NXF1-dependent nuclear export of C9ORF72 transcripts retaining expanded hexanucleotide repeats and reveal a novel promising therapeutic target for neuroprotection.